PERANCANGAN SISTEM INFORMASI AKUNTANSI PENDAPATAN BERBASIS WEB PADA SATUAN PELAYANAN PENGEMBANGAN INDUSTRI PERTEKSTILAN BANDUNG - Willi Ihzan Maulana; Perwito; Candra Mecca Sufyana; Anggi, Sri Anggi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
he development of the industry requires an effective and efficient accountingsystem of revenue to be used during the pandemic to minimize direct contect withicm ( a small medium industry) at the disposal of machine-services, current systemsusing a miscrosoft word for record keeping and data strorage, running systems alsohave no such directly intergrated databases that when creating an income statement,it has to manually enter the data to address revenue issues and make icm easier. Theaim of this study is to build web based pertying-income accounting systems onbandung industrial development project, the methods used in research arequalitative methods with data collection techniques observation, interviews,documentation, library study and system development methods using waterfall